A Preliminary study on the relationship between psychographic factors and the purchase of life insurance - Tan, Suang Sin; Lim, Chee Chee (Universiti Utara Malaysia, 2017)
This was a preliminary study conducted to examine the relationship between psychographic factors (i.e., personal value, risk attitude, and trust) and the purchase of life insurance among Alor Setar city folks.A non-probability convenience sampling technique was used to collect data from early February to mid-March 2015.A sample comprising 108 respondents were subjected to binary logistic regression analysis. The major finding of this study showed that risk attitude has a significant and negative relationship with the purchase of life insurance.Respondents in Alor Setar who are more likely to involve in risky behaviours or activities tend not to buy life insurance.Risk taking individuals do not behave like risk averse individuals who tend to seek protection by buying life insurance as a method to cover their personal risks.Meanwhile, personal value and trust were found to have no significant relationship with the purchase of life insurance among respondents in Alor Setar. It is recommended that a comprehensive study covering wider areas with larger sample sizes be included in future studies to obtain more reliable results that would enable the generalisation of findings.